Human mesenchymal stem cells lose their functional properties after paclitaxel treatment - Münz, Franziska; Lopez Perez, Ramon; Trinh, Thuy; Sisombath, Sonevisay; Weber, Klaus-Josef; Wuchter, Patrick; Debus, Jürgen; Saffrich, Rainer; Huber, Peter E.; Nicolay, Nils (Scientific reports, 2018)
Mesenchymal stem cells (MSCs) are an integral part of the bone marrow niche and aid in the protection, regeneration and proliferation of hematopoietic stem cells after exposure to myelotoxic taxane anti-cancer agents, but the influence of taxane compounds on MSCs themselves remains incompletely understood. Here, we show that bone marrow-derived MSCs are highly sensitive even to low concentrations of the prototypical taxane compound paclitaxel. While MSCs remained metabolically viable, they were strongly impaired regarding both their proliferation and their functional capabilities after exposure to paclitaxel. Paclitaxel treatment resulted in reduced cell migration, delays in cellular adhesion and significant dose-dependent inhibition of the stem cells’ characteristic multi-lineage differentiation potential. Cellular morphology and expression of the defining surface markers remained largely unaltered. Paclitaxel only marginally increased apoptosis in MSCs, but strongly induced premature senescence in these stem cells, thereby explaining the preservation of the metabolic activity of functionally inactivated MSCs. The reported sensitivity of MSC function to paclitaxel treatment may help to explain the severe bone marrow toxicities commonly caused by taxane-based anti-cancer treatments.
Gesehen am 21.05.2019